Exploring the Tourism Culinary Experiences: an Investigation of Tourist Satisfaction in Ubud - Sucita Yanthy, Putu (Udayana Journal of Social Sciences and Humanities; Vol 2 No 1 (2018): UJoSSH, Feburary 2018DO - 10.24843/UJoSSH.2018.v02.i01.p05, 2018)
Food has always been part of people?s life,as it has a major role for people. Food can create a memorable experience, especially for tourists who travel with the purpose of seeking new dishes and experiences. Ubud is one of the best destinations in Bali. It has a lot of warung (small eateries) and restaurants. The local food most easily found in this destination ranges from babi guling (suckling pig) to organic food. By drawing a connection between the local food and tourist experience, this research reveals tourist satisfaction and the importance of culinary elements in the development of Balinese dishes in Ubud. In the analysis, the findings are divided into four quadrants describing tourist satisfaction and the importance of culinary elements that refer to nineteen elements. In conclusion, the culinary industry in Ubud has developed fast, and the tourist satisfaction is mainly affected by the efforts of cultural preservation made by the small eateries and restaurants in Ubud.